2016
DOI: 10.1038/nchem.2684
|View full text |Cite
|
Sign up to set email alerts
|

Control over differentiation of a metastable supramolecular assembly in one and two dimensions

Abstract: Molecular self-assembly under kinetic control is expected to yield nanostructures that are inaccessible through the spontaneous thermodynamic process. Moreover, time-dependent evolution, which is reminiscent of biomolecular systems, may occur under such out-of-equilibrium conditions, allowing the synthesis of supramolecular assemblies with enhanced complexities. Here we report on the capacity of a metastable porphyrin supramolecular assembly to differentiate into nanofibre and nanosheet structures. Mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
408
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(435 citation statements)
references
References 48 publications
17
408
1
6
Order By: Relevance
“…1315 Exciting examples are found in kinetically controlled living copolymerizations as developed for covalent block copolymers 11e−11h and small molecules, 13c−13g which show that kinetically trapped block structures can be formed in supramolecular copolymers. For systems under thermodynamic equilibrium, a combined experimental and theoretical approach proved to be a robust method to unravel several issues, although these endeavors were typically limited to one-component or simple two-component systems.…”
Section: Introductionmentioning
confidence: 99%
“…1315 Exciting examples are found in kinetically controlled living copolymerizations as developed for covalent block copolymers 11e−11h and small molecules, 13c−13g which show that kinetically trapped block structures can be formed in supramolecular copolymers. For systems under thermodynamic equilibrium, a combined experimental and theoretical approach proved to be a robust method to unravel several issues, although these endeavors were typically limited to one-component or simple two-component systems.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported ao ne-cycle zero-dimensional/one-dimensional conversion of pyrenemodified dendritic self-assembly between vesicles and nanotubes induced by the sequential addition of cyclodextrin (CD) and poly(propylene glycol). [11] Herein, we report ap hotocontrolled, reversible,a nd repeatable nanotube-nanosheet, that is,o ne-dimensional/twodimensional, morphological conversion of the supramolecular assembly of adamantanyl-modified diphenylalanine (Ada-FF)w ith azobenzene-bridged bis(b-CD) (H; Scheme 1). [10] More recently,T akeuchi and Sugiyasu et al achieved one-and two-dimensional supramolecular assemblies (nanofibers/nanosheets)v ia control of the kinetic self-assembly process of ametastable porphyrin.…”
mentioning
confidence: 99%
“…So far, the growth of supramolecular polymers is considered to be one-dimensional (1D) in nature, however, recently, two-dimensional (2D) growth by seeded supramolecular polymerization approach has been realized. 14,15 Therefore, understanding the pathway complexity and the mechanistic details of supramolecular polymerization has created great opportunities for researchers to design functional supramolecular assemblies similar to that of several biological systems. 1620 Porphyrin, squaraine, Bodipy, rylene and cyanine dyes, etc.…”
Section: Introductionmentioning
confidence: 99%